2019
DOI: 10.1007/s40843-018-9397-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards the gemini cation anion exchange membranes by nucleophilic substitution reaction

Abstract: As a critical component of alkaline fuel cells, anion exchange membranes determine the energy efficiency, output power density and the long term stability. Recently, the anion exchange membranes with gemini-cation side chains exhibit superior ion conductivity due to their good nanophase separation. However, the costly and complicated synthesis limits their scaling up and commercialization. To address this problem, a convenient synthetic procedure under mild conditions is well developed. A tertiary amine precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…52,53 The To compare our membranes with recently reported AEMs, we summarize the AEMFCs peak power densities as a function of room temperature OH − conductivities for recently reported AEMs that based on similar aryl ether-containing polyaromatics backbone (Figure 4g and Table S2). 9,20,21,47,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] And our QA38PPO-P membrane show a competitive OH − conductivity and fuel cell performance among these AEMs. This highlights the advantages of developing AEMs containing well-defined cation-dipole interaction networks, which can form inter-connected ionic channels that facilitate ion transport.…”
Section: Simulation Studiesmentioning
confidence: 89%
“…52,53 The To compare our membranes with recently reported AEMs, we summarize the AEMFCs peak power densities as a function of room temperature OH − conductivities for recently reported AEMs that based on similar aryl ether-containing polyaromatics backbone (Figure 4g and Table S2). 9,20,21,47,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] And our QA38PPO-P membrane show a competitive OH − conductivity and fuel cell performance among these AEMs. This highlights the advantages of developing AEMs containing well-defined cation-dipole interaction networks, which can form inter-connected ionic channels that facilitate ion transport.…”
Section: Simulation Studiesmentioning
confidence: 89%
“…The side chains promote the formation of interconnected ion‐conducting channel, which results in high ion conductivity. On this basis, we further optimized the side chain structure by increasing the number (two or three) of the cationic groups (Figures 4c, 4d), [ 32‐33 ] and found that the multi‐functionalized side chains will aggregate together easier to form the well‐connected ion‐conducting channel, the ion transfer efficiency was much higher when introducing three cations in side chain, with hydroxide conductivity of 69 mS/cm at room temperature, which is comparable to that of the proton exchange membrane Nafion. It demonstrated a facile but efficient strategy to design highly OH − conductive IEMs.…”
Section: Ion Exchange Membrane Preparationsmentioning
confidence: 99%
“…Quaternary ammonium-functionalized AEMs are the most widely researched because of their good hydrophilicity and high anion conductivity [27][28][29][30]. Generally, they can be synthesized by two reaction routes: (1) post-halomethylation of polymer precursors followed by quaternization [31][32][33] or (2) direct polymerization of quaternary ammonium-or amine-containing monomers [34][35][36].…”
Section: Introductionmentioning
confidence: 99%